Seletividade de herbicidas inibidores do fotossistema II para cultivares de cana-de-açúcar - Simões, P. S. [UNESP]; Carbonari, C. A. [UNESP]; Nascentes, R. F. [UNESP]; Stasievski, A. [UNESP]; Velini, E. D. [UNESP] (FapUNIFESP (SciELO), 2016)
For the successful execution of chemical weed control in sugarcane crop, the selectivity of herbicides is a factor of great importance to maximize crop yield. Each cultivar may respond differently to the same herbicide in the same dose, and selectivity is not only determined by the visual presence or absence of phytotoxicity. Thus, the aim of this study was to evaluate the effects of herbicides amicarbazone, tebuthiuron, and diuron + hexazinona on the electron transport rate in photosystem II (ETR), along with the development and yield of sugarcane cultivars RB867515, CTC 4, CTC 9, and CTC 17 in greenhouse, and field conditions. Under greenhouse conditions ETR was assessed by a portable fluorometer, aa well as dry weight and phytotoxicity of the plants. In field evaluations, ETR, number of stems, yield and technological characteristics were assessed. In the greenhouse, the tebuthiuron herbicide caused the lowest reduction levels of ETR, phytotoxicity and dry weight of different sugarcane cultivars, followed by amicarbazone, and diuron + hexazinona. The effects of herbicides in ETR and phytotoxicity were more intense in greenhouse conditions than in field conditions for all cultivars. Herbicides tebuthiuron, amicarbazone and diuron + hexazinoa were selective for all evaluated cultivars, and reductions in the ETR after herbicide application did not affect the yield and technological characteristics of sugarcane cultivars.
Selectivity of herbicides inhibitors of photosystem II for sugarcane cultivars
Keywords: Amicarbazone; Diuron; Electron transport rate; Hexazinona; Saccharum spp; Tebuthiuron